Figures mythiques et histoire. Réinterprétations et contrastes entre Orient et Occident - Denise Aigle (Revue des Mondes Musulmans et de la Méditerranée)
The history of the Islamic East is marked by great personages who are considered as models and Founding Fathers. Some of them are of Islamic origin, others have been inherited from Antiquity or the Bible. These characters have undergone a certain number of changes from the 10th century onward, basically because of the influence of the Shäh-nâma at a time when independent dynasties were proliferating and later with the breakthrough of the Turks, the Crusaders and the Mongols. The figures of Saladin and Chinggis Khan illustrate the renewal of ancient models, their extension and their successive reinterpretations. Mythical creativity seems to have been a cultural activity closely linked to political aims. The life of a conqueror such as Tamerlane has been set as a model by imitators who thus wished to justify their territorial claims. The biblical references attested to in the Quran allowed for the integration of the Turks and later of the Mongols into the history of the Creation as descendants from one of Noah's three sons. Ancient biblical events have also attributed a certain importance to the Muslims of the Volga area from the 18th century onward as well as to the various Christian and Muslim communities of the Caucasus. In fact, biblical references to this region abound such as the beaching of Noah's ark on Mount Ararat or the imprisonment of Gog and Magog behind the iron gates.